Menumbuhkan Literasi Teknologi dan Pengembangan Potensi Akademik dan Nonakademik Siswa melalui Pengenalan AI di SMA Negeri 2 Bitung - Taju, Semmy Wellem; Moedjahedy, Jimmy; Adam, Stenly Ibrahim; Rotikan, Reymon (Universitas Klabat, 2025)
Artificial Intelligence (AI) has rapidly emerged as a central pillar in the transformation of education in the digital age. This program Pengabdian kepada Masyarakat (PKM) aims to introduce AI technology as an innovative tool in developing the academic and non-academic potential of students at SMA Negeri 2 Bitung. This activity is carried out in the form of an interactive introduction, demonstration of the latest AI applications (examples such as ChatGPT, Copilot and Gemini), as well as assistance in the use of AI in personalized learning, development of critical thinking skills, communication, collaboration and even adaptability. The methods used include participatory and problem-based approaches to encourage active involvement of SMA Negeri 2 Bitung students. As a result, students showed improved understanding of AI concepts and their practical applications, along with a growing interest in exploring digital technologies more deeply. With this activity, it is hoped that it can be a starting point for building an AI technology-based learning environment in schools, as well as creating a young generation that is more adaptive and ready to face the challenges of technological change.